Family caregivers’ experience in providing home-based palliative care: A descriptive phenomenological study - Karolin Adhisty; Mutia Nadra Maulida; Siti Sarahdeaz F; Zesi Aprilia (School of Health Sciences Al-Ma'arif, 2026)
Background: Families, as a vital part of palliative care, need to be identified and their roles and functions explored in order to improve patients’ quality of life at home following hospitalisation. Objective: This study aims to identify the current situation regarding patient care at home. Methods: The method used in this study was a qualitative approach employing a descriptive-phenomenological methodology. informants were selected based on purposive sampling criteria, with a total of nine informants. Interviews were conducted using a semi-structured interview technique, in the Sakatiga Village Health Center. Results: The results of this study indicate that experiences of caring for palliative care patients vary; families, as a vital part of patient care, must be able to provide care for patients, even though family carers are likely to face various challenges, such as a lack of knowledge regarding care provision. The findings further examine the conditions of care provided at home, including: the assessment of the patient’s and family’s condition; the patient’s complaints regarding their condition; the family’s feelings towards the patient’s condition; the family’s coping mechanisms; dilemmas in meeting the patient’s care needs; and medical information required to understand the patient’s condition. Conclusion: The results of this study indicate that families in providing palliative care need a forum to discuss, talk, and express their feelings while providing patient care at home. This is necessary because apart from being an important part of care, families are also required to always be able to carry out their functions optimally.